SUMBER DAYA MANUSIA SEBAGAI SUMBER KEUNGGULAN KOMPETITIF - Kasmawati Kasmawati (Universitas Islam Negeri Alauddin Makassar, 2018)
AbstrakThe competition between companies or institutions today requires companies or institutions to be able to survive and compete with other companies. One of the things that can be taken by the company to be able to survive in intense competition is human resources. The role of human resources in the company is very important because the main driver of all activities the company in achieving its goals both to gain profits and to maintain the survival of the company are humans. The success or failure of a company in maintaining the existence of the company starts from the human effort itself in maximizing effectiveness and efficiency. In other words, the performance of an organization or company is highly influenced and even depends on the quality and competitive ability of its human resources. The purpose of the company in standardizing or benchmarking so that human resources or labor obtained can really work in accordance with what is desired by the company.